Association between disease activity of rheumatoid arthritis and maternal and fetal outcomes in pregnant women: a systematic review and meta-analysis - Jiamin Lv; Li Xu; Shuhui Mao (BMC, 2023)
Abstract Background A meta-analysis has compared the pregnancy outcomes between women with and without RA, while the effect of disease severity on pregnancy outcomes within women with RA has not been explored. Therefore, we performed a systematic review and meta-analysis to assess the association between disease activity of RA and pregnancy outcomes. Methods Four English databases (Pubmed, Embase, Cochrane Library, and Web of Science) and three Chinese databases (China National Knowledge Infrastructure [CNKI], VIP, and Wan Fang) was searched for eligible studies up to August 13, 2023. Cochran's Q test and the I2 statistic were used to assess the heterogeneity of the included studies. The odds ratio (OR) (for counting data) and weighted mean difference (WMD) (for measurement data) were calculated with 95% confidence intervals (95%CIs) using random-effect model (I2 ≥ 50%) or fixed-effect model (I2 < 50%). Subgroup analysis based on study design and regions was used to explore the sources of heterogeneity. Sensitivity analysis was performed for all outcomes and the publication bias was assessed using Begg's test. Results A total of 41 eligible articles were finally included. RA women had higher odds to suffer from preeclampsia, gestational diabetes, spontaneous abortion, and cesarean delivery (all P < 0.05). The infants born from RA mother showed the higher risk of stillbirth, SGA, LBW, congenital abnormalities, diabetes type 1, and asthma (all P < 0.05). The high disease activity of RA was significantly associated with the higher risk of cesarean delivery (OR: 2.29, 95%CI: 1.02-5.15) and premature delivery (OR: 5.61, 95%CI: 2.20-14.30). Conclusions High disease activity of RA was associated with the high risk of adverse pregnancy outcomes, suggesting that it was important to control disease for RA women with high disease activity who prepared for pregnancy.